Lexicons Used in the Traditional Gamelan of Jegog in Sangkaragung Village - Putri, Ni Putu Aprilananda Suganda; Budasi, I Gede; Swandana, I Wayan (Universitas Muhammadiyah Magelang, 2026)
Language and culture are inseparable aspects of human life, as language functions not only as a communication tool but also as a medium for preserving cultural understanding. The traditional gamelan of Jegog is a traditional bamboo gamelan that is originated from West Bali, and Sangkaragung Village in Jembrana Regency is the conservation center of Jegog gamelan. This study aims to (1) identify the lexicons used in the traditional gamelan of Jegog in Sangkaragung Village and (2) to analyze the cultural meaning used in the identified lexicons. This study employed a qualitative descriptive research design. The data were collected in Sangkaragung Village through observation and in-depth interviews with four selected informants. The instruments used in this study were observation sheets, interview guide, interview sheets, and smartphones. This study found thirty-five (35) lexicons in the traditional gamelan of Jegog in Sangkaragung Village that can be classified into six categories namely, instrument names, techniques in playing Jegog, sound quality and tuning concepts, sequence of playing Jegog, types of tabuh, and ritual before doing Jegog performance. Each of the identified lexicons carry cultural meaning that reflects the harmony, tradition, and beliefs of Sangkaragung people. The findings of this study emphasize the importance of preserving the lexicons in Jegog gamelan as an effort in preserving local identity and sustaining cultural continuity in the era of globalization. This study can contribute to linguistic studies, particularly in teaching cross-cultural understanding and as an effort to preserve Balinese language and culture.